The Treatment Algorithm in Diabetic Foot: An Alternative Against Amputation? - Tacettin Güçer (European Medical Journal)
This clinical treatment modality was applied to 62 diabetic ulcers on lower extremities for which surgeons had been advised amputation. Total healing was achieved in 53 of them and was achieved through this treatment in a 3-month period. The remaining nine cases also showed improvement in healing at different levels, but they were not accepted as a ‘satisfactory result’. This treatment modality contains a synthetic prostacyclin analogue, two different phosphodiesterase inhibitors, a peripheral revascularisation agent, another agent increasing peripheral resistance to ischaemia, and a polysaccharide with positive rheologic properties on capillary circulation. Therefore, this treatment was found to be effective on circulation of the extremities, with radiologically-proven insufficient blood supply. The treatment also had a positive effect on recirculation and effects on collateral revascularisation through mechanical vacuum application, modified from standard vacuum treatments. With this combination, this technique was found extremely effective by application, according to the algorithm explained below, and should be an alternative to the current therapy applications in diabetic ulcers.